High‐Aspect‐Ratio Parallel‐Plate Microchannels Applicable to Kinetic Analysis of Chemical Vapor Deposition. Issue 16 (7th July 2016) - Shima, Kohei; Funato, Yuichi; Sugiura, Hidetoshi; Sato, Noboru; Fukushima, Yasuyuki; Momose, Takeshi; Shimogaki, Yukihiro
Abstract : A method is proposed to fabricate a high‐aspect‐ratio (HAR) microchannel with a microscopic gap and AR of more than 1000:1 applicable to a test structure for kinetic analysis of chemical vapor deposition (CVD). It has a parallel‐plate structure and is formed concisely by sticking a planar Si substrate and a patterned Si or silicon‐on‐insulator (SOI) substrate fabricated by single‐step etching, by clamping them. The resulting feature exhibits a uniform gap and smooth surface morphology along its depth. When CVD is conducted into this HAR microchannel, the sticking probability ( η ) of film‐forming species can be detected by analyzing the film thickness gradient. The use of a microchannel with an AR of 1000:1 enables the elucidation of η values from 1 down to the order of 10 −7 . A kinetic analysis of SiC‐CVD from methyltrichlorosilane and H2 is thus performed. It is found that conformal SiC‐film growth occurred inside the HAR microchannel, where one of the film‐forming species is revealed to have extremely low η around 10 −6 . The present study demonstrates that the developed HAR microchannel is a solution to access the overall reaction kinetics of CVDs, including film‐forming species with extremely low η . Abstract : A very deep microchannel with aspect ratio ≥1000:1 is developed as a test structure for kinetic analysis of chemical vapor deposition (CVD). When CVD is conducted into the microchannel, the sticking probability of film‐forming species can be detected in the range from 1 down to the order of 10 −7, by analyzing the film‐thickness gradient.